Digital Tourism and the Recovery of International Tourist Arrivals to Indonesia Post-COVID-19 - Ramdani, Dadan (Journal of Economics and Management Scienties, 2025)
The COVID-19 pandemic caused an unprecedented collapse in international tourism, severely impacting Indonesia’s visitor-dependent economy. In response, tourism stakeholders accelerated the adoption of digital solutions to mitigate losses and stimulate recovery. This study investigates how digital tourism has influenced the rebound in international tourist arrivals to Indonesia between 2020 and 2024. Employing a systematic literature review, the analysis identifies four key themes: digital marketing and destination branding, virtual tourism platforms, mobile-based and contactless services, and policy-driven digital readiness. Findings show that digital innovations played a crucial role in restoring destination visibility, traveler trust, and operational adaptability. However, their impact was uneven due to infrastructural disparities, digital literacy gaps, and inconsistent policy execution. The study concludes that while digital tourism fosters resilience and competitiveness, its long-term success requires inclusive infrastructure, inter-institutional coordination, and strategic national integration.